The age of global economic crises : (1929-2022) - Matés Barco, Juan Manuel; Vázquez Fariñas, María (New York, NY : Routledge, 2023)
"The frequency and repetition of economic crises over the last hundred years demands an analysis that allows us to discover the root causes of these situations and the problems they have generated in the world economy. This book investigates these cycles throughout the 20th and the early 21st century. Economic crises can be the result of political or military conflict, but they have also been the consequence of bad practices, unbridled speculation, excessive greed or poor management by the rulers and leaders of nations. The contributors to this volume analyse the causes and consequences of economic crises from the Great Depression to the present day, incorporating post-World War II reconstruction, the oil crisis of the 1970s and the "lost" Latin American decade of the 1980s, among others. This longer-term view allows the book to provide insights into understanding economic cycles in the long run, not just at a specific moment in time, and the ways in which they have spread internationally. This historical analysis also helps to shed new light on the current covid-impacted situation, as it provides another reading of the main crises of recent centuries and their causes and consequences, as well as the measures and policies adopted to overcome the difficulties. This book will be of significant interest to readers in economic history, business history, politics, and economics and history more broadly"--
OCLC-licensed vendor bibliographic record.
Keywords: Financial crises -- 20th century; Financial crises -- 21st century; BUSINESS & ECONOMICS / Economic History; BUSINESS & ECONOMICS / Economics / General